The Effectiveness of Utilization WhatsApp Application As Media Discussion (Study of â€œKelas Prestasiâ€ Community in the Scope of University of Bengkulu) - Usman, Ujang; Arwani, Marwan; Samosir, Fransiska Timoria (Record and Library Journal, 2020)
Background of the study: The student in â€œKelas Prestasiâ€ Community in University Bengkulu uses the WhatsApp in daily communication in discussion.Purpose: The research about "The effectiveness of Utilization WhatsApp application as Media discussion" aims to determine the extent of the effectiveness of using the WhatsApp application as a medium of daily communication to be a media discussion by the â€œKelas Prestasiâ€ Community on the scope of University of Bengkulu in organized activities.Method: This research has used a qualitatively descriptive method. The process of collecting research data has been conducted through in-depth interview techniques, observations, and direct documentation.Findings: The use of the WhatsApp application as a media discussion has added the ability to change the participants of the discussion on aspects of insight, conprehensen, skill and attitude. Insight is about new information or views obtained after the discussion process. Then, the aspect of understanding, learners reveals that they are capable of translating so as to understand the issues discussed and conclude the outcome of the discussion activities. Furthermore, the aspect of the skill gets the fact that they can communicate interactively or to speak to each other and be able to take steps to see and solve problems. The last of these aspects of attitude also gets the fact that the participants of the discussion feel a change in their self, such as a change in confidence and a sense of tolerance in seeing a difference, especially disagreements.Conclusion: The results of this research show that the use of WhatsApp applications as a media discussion seen from the four aspects has been effective.